Friends of the court : the privileging of interest group litigants in Canada - Brodie, Ian (Ian Ross) (SUNY series in American constitutionalism., 2002)
"In this book-length study of interest group litigation in Canada, Friends of the Court traces the Canadian Supreme Court's ever-changing relationship with interest groups since the 1970s. After explaining how the Court was pressured to welcome more interest groups in the late 1980s, Brodie introduces a new theory of political status describing how the Court privileges certain groups over others. By uncovering the role of the state in encouraging and facilitating litigation, this book challenges the idea that interest group litigation in Canada is a grassroots phenomenon."--Jacket